Stress promotes Arabidopsis - Piriformospora indica interaction. (3rd May 2016) - Vahabi, Khabat; Dorcheh, Sedigheh Karimi; Monajembashi, Shamci; Westermann, Martin; Reichelt, Michael; Falkenberg, Daniela; Hemmerich, Peter; Sherameti, Irena; Oelmüller, Ralf
ABSTRACT: The endophytic fungus Piriformospora indica colonizes Arabidopsis thaliana roots and promotes plant performance, growth and resistance/tolerance against abiotic and biotic stress. Here we demonstrate that the benefits for the plant increase when the two partners are co-cultivated under stress (limited access to nutrient, exposure to heavy metals and salt, light and osmotic stress, pathogen infection). Moreover, physical contact between P. indica and Arabidopsis roots is necessary for optimal growth promotion, and chemical communication cannot replace the physical contact. Lower nutrient availability down-regulates and higher nutrient availability up-regulates the plant defense system including the expression of pathogenesis-related genes in roots. High light, osmotic and salt stresses support the beneficial interaction between the plant and the fungus. P. indica reduces stomata closure and H2 O2 production after Alternaria brassicae infection in leaves and suppresses the defense-related accumulation of the phytohormone jasmonic acid. Thus, shifting the growth conditions toward a stress promotes the mutualistic interaction, while optimal supply with nutrients or low stress diminishes the benefits for the plant in the symbiosis.